Adherence to the Mediterranean Diet for a Better Sperm Quality: A Comprehensive Systematic Review and Meta-Analysis - Munawwir, Abdul; Adhani, Zalsabila Tiara (Jurnal Gizi dan Pangan, 2025)
The aim of this study is to investigate whether a higher adherence to the Mediterranean Diet (MD) can enhance reproductive indicators in infertile men. A comprehensive review and meta-analysis were conducted to assess whether increased adherence to the MD can enhance reproductive indicators in infertile men. An extensive search was conducted for pertinent studies in PubMed, Medline, and Google Scholar. The search included relevant publications published in the last 10 years from 2015. The Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) 2020 instrument was used to evaluate the studies. The study's quality was evaluated using the Newcastle-Ottawa Scale (NOS). The data were analyzed and evaluated using RevMan version 5.4.1. The data on sperm volume were not statistically significant. The meta-analysis indicated an odds ratio of 1.06 for low semen volume (<1.5 mL) associated with low adherence to the MD (I2=12%; 95% CI:0.59–1.93, p=0.84). Furthermore, the analysis revealed a 2.86-fold increase in the probability of achieving higher sperm concentration (>15 × 106/mL) in individuals who adhered to the MD (I2=33%; 95% CI:1.58–5.18, p=0.0005). The meta-analysis further suggests that adherence to the MD is associated with a 2.54-fold increase in the likelihood of improving sperm count (>39 × 106/ejaculate) (I2=48%; OR=2.54; 95% CI:1.32–4.90, p=0.005). The meta-analysis on sperm motility demonstrated that individuals who adhere strictly to the MD are more likely to exhibit normal motility (>40%) (I2=0%; OR=4.64; 95% CI:2.41–8.95, p<0.00001). The meta-analysis further revealed a 2.66-fold increased likelihood of better sperm morphology (>4%) (I2=0%; OR=2.66; 95% CI:1.39–5.10, p=0.003) in individuals adhering to the MD. The present systematic review with meta-analysis indicates that higher adherence to the MD is associated with improved sperm quality parameters (sperm count, sperm concentration, sperm motility, and sperm morphology).